Pengaruh Loan To Deposit Ratio (LDR), Biaya Operasional, Pendapatan Operasional (BOPO), Kurs, Capital Adequacy Ratio, Ukuran Bank Dan Inflasi Terhadap Non Performing Loan (NPL) Di Perusahaan Perbankan Terdaftar Di BEI - Bayu Wulandari; Khetrin Khetrin; Ketryn Seviyani (Journal of Economic, Bussines and Accounting (COSTING), 2021)
Financial institutions that provide financial services are known as banking. The purpose of this research is to test and analyze the effect of LDR, BOPO, exchange rate, CAR, bank size and inflation on NPL in banking companies listed on the Indonesia Stock Exchange. The method is quantitative research. This research is explanatory. The research data is classified as quantitative and ratio scale. Data is collected by means of documentation. The population is 45 banks listed on the IDX for the period 2014-2018. The sample is 125 financial statements of banking companies listed on the Indonesia Stock Exchange for the period 2014-2018. The model is multiple linear regression. The results of the study are LDR, BOPO, Exchange Rate, CAR, Bank Size and Inflation have no simultaneous and partial effect on NPL in banking companies listed on the Indonesia Stock Exchange. Keywords: Loan to Deposit Ratio (LDR), Operating Cost of Operating Income (BOPO), Exchange Rate, Capital Adequacy Ratio, Bank Size, Inflation and Non Performing Loan (NPL).